Metode Pembelajaran Poster Comment Sebagai Upaya Meningkatkan Keterampilan Berbicara Siswa Pada Mata Pelajaran Bahasa Indonesia Kelas III SDN 1 Kolono - Yuni Sara; Ridwan Ardi; Ashari Usman (Journal of Humanities, Social Sciences, and Education, 2025)
This classroom action research aims to improve the learning outcomes of Indonesian language of grade III students of SDN 1 Kolono through the application of the Poster Comment method. The implementation of the action was carried out in two cycles. In cycle I, the learning outcomes showed that 62.50% or 15 out of 24 students achieved a score of ≥ 70, with an average score of 64. This result has not met the established success indicator, which is a minimum of 80% of students completing the learning. Therefore, improvements were made in cycle II. The results in cycle II showed a significant increase, with 83.33% or 20 students completing and the average score increasing to 74.70, so that the success indicator was achieved. In addition, the results of observations of teacher and student activities in cycle I showed many aspects of learning that had not been optimally implemented. After reflection and improvements, observations in cycle II showed that all aspects of learning had been implemented well, with a level of implementation reaching 95%, so that the indicators of success of learning activities were also met. Thus, the Poster Comment method has proven effective in improving learning outcomes and Indonesian language learning activities in grade III students